Land and Legacy: Investigating Horizontal Conflicts in the Short Story "Dataran Melengen" through Postcolonial Ecocriticism Framework - Hidayani, Vini; Alung, Alung; Nasution, Riandry Fadilah (POETIKA, 2024)
The issue of ecology in former colonies is an inevitable consequence of past colonialism. The difference now is that the “colonial” subjects have transformed into multinational corporations that exploit nature and people by seizing the land on which communities depend for their livelihoods. This land grabbing is sanctioned by Indonesia through the legalization of laws that allow capitalism to flourish, while local communities become increasingly impoverished. This ecological issue is depicted in literature that critically addresses environmental issues. Therefore, this study examines the short story “Dataran Melengen” (2003) by Korrie Layun Rampan, which actively portrays the ecological issues in Kalimantan caused by companies holding Forest Concession Rights. This research actively employs postcolonial ecocriticism theory by Graham Huggan and Helen Tiffin as its formal framework and critically analyzes the text using Fairclough's critical discourse analysis method. This theory extensively discusses ecological issues in postcolonial countries, highlighting how state approval and abuse of power contribute to these issues. The study reveals ecological issues within the Dataran Melengen community, including horizontal conflicts driven by poverty, along with cultural loss, terror, and trauma. The short story “Dataran Melengen” serves two key functions as mentioned by Huggan and Tiffin: aesthetic and advocacy. These functions are expected to catalyze a third function—activism—where literature can drive social change. The research process involved a close reading of the text, contextual analysis, and a critical discourse approach to explore the interplay between narrative, power, and ecology.